Plants and human conflict - Pichersky, Eran; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
Perhaps the least appreciated dramatis personae in human history are plants. Humans, like all other animals, cannot produce their own food as plants do through photosynthesis, and must therefore acquire organic material for survival and growth by eating plants or by eating other animals that eat plants. Humans depend on plants not only as a food source, but also as building and clothing materials and as sources of medicines, psychoactive substances, spices, pigments, and more. With plants being such valuable resources, it is therefore not surprising that plants have been involved in practically all violent conflicts among different human societies. Ironically, plants have also been the source of materials to construct weapons or weapon parts. Wars have always constituted a large part of human history, and the overall theme of this book is that to understand the history of violent human conflict, we need to understand what specific materials plants make that people find so useful and worth fighting over, and what roles such plant products have played in specific conflicts. To do so, Plants and Human Conflict begins with a chapter explaining the basic biological facts of the interdependence between plants and humans, and the subsequent seven chapters describe the physical and chemical properties of specific plant products demonstrating how the human need for these products has led to wars as well as contributed to the prosecution of wars. These chapters recount some well-known (and some lesser known) historical events in which plants have played a central role. This book uniquely combines the modern scientific knowledge of plants with the human history of war, introducing readers to a new paradigm that will make them reconsider their understanding of human history, as well as to bring about a greater appreciation of plant biology.
chapter Natural Resources as Causes of Violent Conflicts / Pichersky Eran -- chapter Fighting Grains / Pichersky Eran -- r Pichersky Eran -- r
Keywords: TECHNOLOGY & ENGINEERING / Agriculture / General; Plants and civilization; Plants and history; War